A High‐Performing Asymmetric Supercapacitor of Molybdenum Nitride and Vanadium Nitride Thin Films as Binder‐Free Electrode Grown through Reactive Sputtering. Issue 10 (18th August 2020) - Adalati, Ravikant; Kumar, Ashwani; Kumar, Yogesh; Chandra, Ramesh
Abstract : Transition‐metal nitride (TMN) thin‐film‐based electrodes are recognized for high‐performance, stable, flexible, and smart supercapacitors (SCs), as they exhibit extensive voltage range, good sustainability, and high electrical conductivity. Herein, using reactive DC magnetron sputtering, molybdenum nitride (Mo2 N) and vanadium nitride (VN) thin films are deposited on 304 stainless steel substrate at 200 °C for asymmetric SC (ASC) applications. ASC is constructed using VN@SS as negative electrode and γ ‐Mo2 N@SS as positive electrode and examines the electrochemical behavior in aqueous solutions of 1 m Na2 SO4 at several scan rates and current densities. To scrutinize the crystallographic details and electronic configuration of as‐deposited thin‐film electrodes, X‐ray diffraction and X‐ray photoelectron spectroscopy are used. To visualize the surface morphology, film thickness, and elemental composition, field‐emission scanning electron microscopy and energy dispersive X‐ray analysis is used. The results imply that TMN thin‐film‐based electrodes bestow super‐hydrophilic nature and give enhanced capacitance value along with excellent rate performance. This work demonstrates VN@SS and γ ‐Mo2 N@SS thin‐film‐based electrode for ASC, which show a high capacitance of ≈85.50 Fg −1 and a high specific power of ≈23.3 Wh kg −1 with a broadened voltage window of ≈1.4 V, and this is a potential candidate for energy storage devices. Abstract : Binder‐free transition metal electrode (molybdenum nitride (γ ‐Mo2 N) and vanadium nitride [VN]) is deposited by DC magnetron sputtering on 304 stainless steel substrate. Furthermore, asymmetric supercapacitor (ASC) (VN//Mo2 N) is constructed and examines electrochemical behavior in an aqueous solutions of 1 m Na2 SO4. The electrochemical test exhibits high specific capacitance with remarkable capacitance retention over 5000 charging discharging cycles.